Assessment of myocardial function in elite athlete`s heart at rest - 2D speckle tracking echocardiography in Korean elite soccer players - Eun, L. Y.; Chae, H. W. (Research Reports, 2016)
The purpose of this study was to investigate Korean elite soccer players` myocardial function using the conventional and advanced speckle tracking imaging to compare the difference with the normal controls. We used 2D echocardiography speckle tracking echocardiography (STE) to evaluate LV regional strain in 29 elite soccer players compared to 29 age-matched healthy controls. Conventional, tissue Doppler, and STI echocardiography was performed, for strain at base and apex, rotation and torsion. There is no difference in longitudinal strain (-17.6 ± 1.8 vs -17.3 ± 2.9, p = ns), and basal radial strain. However, the significant increases were noticed in basal circumferential strain (-17.5 ± 2.6 vs -15.5 ± 8.9, p = 0.05), apical radial strain (33.1 ± 20.5 vs 22.5 ± 19.4, p = 0.02), and apical circumferential strain in soccer players (-21.4 ± 4.8 vs -16.8 ± 7.6, p = 0.005). Soccer players showed the higher rotation at base (-3.9 ± 1.9 vs -2.6 ± 3.2, p = 0.03), and apex (6.98 ± 2.62 vs 6.21 ± 3.81, p = 0.05), higher torsion (10.9 ± 3.7 vs 8.8 ± 6.3, p = 0.05). In conclusion, the elite soccer players` heart demonstrated the unique ventricular adaptation. These alterations could benefit the cardiovascular adjustment to exercise without much loss of myocardial energy expenditure.